﻿Outcomes of the treatment of trigger digits by extracorporal shock wave therapy (ESWT) - Zyluk, Andrzej; Mosiejczuk, Hanna (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
Background Currently, extracorporal shock wave therapy (ESWT) has been widely used in tendinopathies, including trigger fingers.Purpose The objective of this study was evaluation of effectiveness of ESWT for trigger digits in a short and mid-term follow-up.Patients and methods Thirty-two patients, 28 women and 4 men, in a mean age of 60 years, with a total of 50 affected digits underwent local extracorporal shock wave treatment. Each patient received 3 applications in a weekly interval. Results were assessed at 1 week and 3 months follow-up, using numeric rank scale for pain and Froimson scale for clinical severity.Results One-week post-treatment, pain and triggering ceased completely or reduced significantly in 30 patients (94%). At 3 month follow-up, in 30 patients (94%) the symptoms resolved completely and they were considered recovered. Two patients (6%) failed to improve and in these cases the treatment was considered ineffective.Conclusion ESWT is an effective therapy for trigger digits in II° i III° severity grade and may be an alternative for other, noninvasive measures such as physiotherapy or steroid injection.
Keywords: Tendovaginosis stenosans; trigger finger; shock wave therapy